2003
DOI: 10.1055/s-2003-37707
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Ameliorates Cerebral Infarction from Ischemia-Reperfusion Injury in Rats

Abstract: Honokiol, a constituent extracted from Magnolia officinalis, had been shown be an antioxidant and an anti-platelet agent in biological systems with an anti-arrhythmic effect and a myocardial protective effect on ischemia-reperfusion injury. We examined the neuroprotective effect of honokiol in rats subjected to focal cerebral ischemia. Honokiol was administered intravenously either at fifteen minutes before right middle cerebral artery occlusion (pretreatment groups) or when both common carotid arteries clips … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 15 publications
3
43
0
Order By: Relevance
“…The infarct volume induced by CI/R injury in this study (around 20% of the right brain hemisphere) was comparable with that of our previous reports [20,27]. Taxifolin (0.1-1.0 lg/kg) dosedependently ameliorated CI/R-induced brain infarction by 40-65% (Figure 1 upper panel, one-way ANOVA, p<0.05).…”
Section: Protective Effect Of Taxifolin Against Ci/r-induced Cerebralsupporting
confidence: 91%
See 1 more Smart Citation
“…The infarct volume induced by CI/R injury in this study (around 20% of the right brain hemisphere) was comparable with that of our previous reports [20,27]. Taxifolin (0.1-1.0 lg/kg) dosedependently ameliorated CI/R-induced brain infarction by 40-65% (Figure 1 upper panel, one-way ANOVA, p<0.05).…”
Section: Protective Effect Of Taxifolin Against Ci/r-induced Cerebralsupporting
confidence: 91%
“…Twenty-four hours after the surgery, the rats were anesthetized and sacrificed. During the entire experiment, the blood gas data and physiological data were monitored as in our previous report [20]. The experimental grouping included one sham-operated group (sham, n=10), two (0.1 and 1.0 lg/kg) taxifolintreated groups (n=10, for each dose), and one CI/ R group (CI/R only, n=10).…”
Section: Animals and Induction Of Cerebral Ischemic-reperfusion Injurymentioning
confidence: 99%
“…Honokiol has also been found to have a variety of pharmacological action, such as antiinfl ammatory action (22), antithrombotic activity (23), anti-arrhythmic activity (24), neuroprotective activity (15), antioxidative action (25), and anxiolytic action (26). Numerous animal studies have also demonstrated that honokiol acts as an anti-stress agent and a potent suppressor of oxidative damage and cancer (27).…”
Section: Magnolol and Honokiolmentioning
confidence: 99%
“…It is widely used by Chinese people in treating thrombotic stroke, typhoid fever, anxiety and nervous disturbance [1] when used in combination with other herbs. With its major active constituent extracted from the bark of Houpu, honokiol has been found having a variety of pharmacological effects, such as anti-inflammatory [2] , antithrombotic [3] , anti-arrhythmic [4] , antioxidative [5] and anxiolytic effects [6] . Recently, honokiol has been reported to exhibit a potent cytotoxicity by inducing cell apoptosis in rat and human leukemia cells [7,8] , human fibrosarcoma cells [9] , human squamous lung cancer CH27 cells [10] and human SVR angiosarcoma cells [11] , yet there has been no report on honokiol in the treatment of human colorectal carcinoma.…”
Section: Introductionmentioning
confidence: 99%